ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PADA MATERI PERSAMAAN LINEAR SATU VARIABEL KELAS VII SMP NEGERI 3 SUNGAI LALA - Aulia Putri Mahjura; Sri Yunita Ningsih (Ensiklopedia Education Review, 2026)
This study aims to examine students’ ability to comprehend mathematical concepts in the topic of Linear Equations in One Variable (LEOV) at SMP Negeri 3 Sungai Lala. The analysis was carried out on five test items designed to assess students’ conceptual understanding across multiple indicators. Findings revealed that a considerable number of students encounter difficulty in connecting mathematical ideas with appropriate representations and procedures. More specifically, on the first item, a portion of students struggled to restate the LEOV concept in their own words. On the second item, most students tended to skip procedural steps and present only final answers. On the third item, many were unable to follow the given instructions, jumping directly to results without constructing a mathematical model first. On the fourth item, students showed limited ability to distinguish between examples and non-examples of the concept. On the fifth item, students were not able to apply the concept accurately within a problem-solving context, as they lacked a clear strategy for identifying known and unknown elements. Overall, these findings indicate that students’ mathematical conceptual understanding remains at a low level and requires systematic improvement through more structured and concept-oriented instructional approaches.Keywords: mathematical conceptual understanding; linear equation in one variable; mathematical representation; qualitative descriptive; junior high school